Black walnut, Osage orange and eastern redcedar sawmill waste as natural dyes: effect of aluminum mordant on color parameters - Doty, Kelsie; Haar, Sherry J.; Kim, Jooyoun (My University, 2017)
The triple bottom line can be impacted in both positive and negative ways by the use of tree sawmill waste as a natural dye. Trees contain a biomordant in the form of tannin which may eliminate the need for metallic mordants, thus reducing water, thermal energy, residual waste, and exposure to a mordant chemical. Dyeing with mill waste provides an economic option for an existing timber manufacturing byproduct. This research analyzed the impact of potassium aluminum sulfate (PAS) on dye concentration, hue, and colorfastness to light and laundering for three regional dyewoods (black walnut, Osage orange, and eastern redcedar) on wool yarn. Dye concentrations were pre-tested to find a standard depth of shade between mordanted and nonmordanted yarns. Tests for colorfastness to light and laundering were performed according to AATCC methods. Resulting colors for exposed and unexposed specimens were rated using CIE L*a*b* values and descriptive statistics were used to examine directional relationship within independent variables mordant and exposure (light and laundering). Two-sample t test was performed to investigate the effect of a PAS mordant versus no mordant on overall color difference between specimens exposed to light and laundering. Findings indicated that dye absorption was improved with the use of a PAS mordant. For yarns premordanted with PAS the dyewood colors became warmer. A PAS mordant slightly improved colorfastness to light for black walnut and eastern redcedar, but did not influence Osage orange which had a color change from bright yellow to warm brown after exposure to light. Colorfastness to laundering improved only for Osage orange with a PAS mordant.
Citation: Doty, K., Haar, S., & Kim, J. (2016). Black walnut, Osage orange and eastern redcedar sawmill waste as natural dyes: effect of aluminum mordant on color parameters. Fashion and Textiles, 3, 16. doi:10.1186/s40691-016-0074-9
Keywords: Natural Dyes; Mordant; Biomordant; Tannin; Potassium Aluminum Sulfate; Sustainability